Prevalence of Trachoma in Four Local Government Areas of Jigawa State, Nigeria. (28th December 2018) - Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed Dantani; Umar, Murtala Muhammad; Tafida, Abubakar; Ogoshi, Chris; Maidaura, Aminu; Isiyaku, Sunday; William, Adamani; Willis, Rebecca; Bakhtiari, Ana; Olobio, Nicholas; et al.
ABSTRACT: Purpose : To determine the prevalence of trachoma and water and sanitation coverage in four local government areas (LGAs) of Jigawa State, Nigeria: Birnin Kudu, Buji, Dutse and Kiyawa. Methodology : A population-based cross-sectional survey was conducted in each LGA using Global Trachoma Mapping Project (GTMP) protocols. From each LGA, 25 villages were selected using probability-proportional-to-population size sampling; in each village, 25 households were selected using the random walk technique. All residents aged ≥1 year in selected households were examined by GTMP-certified graders for trachomatous inflammation – follicular (TF) and trichiasis, defined according to the WHO simplified trachoma grading scheme definitions. Water, sanitation and hygiene data were also collected through questioning and direct observation. Results : In 2458 households of four LGAs, 10, 669 residents were enumerated. A total of 9779 people (92% of residents) were examined, with slightly more females examined (5012; 51%) than men. In children aged 1–9 years, the age-adjusted prevalence of TF ranged from 5.1% (95% CI 2.5–9.0%) in Birnin Kudu to 12.8% (95% CI 7.6–19.4%) in Kiyawa, while the age- and gender-adjusted trichiasis prevalence in persons aged ≥15 years ranged from 1.9% (95% CI 1.4–2.5%) in Birnin Kudu to 3.1% (95% CI 2.2–4.0) in Dutse. Access to improved water sources was above 80% in all LGAs surveyed but access to improved sanitation facilities was low, ranging from 23% in Buji to 50% in Kiyawa. Conclusion : Trachoma is a public health problem in all four LGAs surveyed. The full SAFE strategy needs to be implemented to achieve trachoma elimination.